Synthesis of Zinc Oxide Nanoparticles Using Aqueous Stem Extract of Colebrookea Oppositifolia Sm: Chracterization and Assessment of Biological Properties - G. C., Bimal; Ojha, Indra; Pusp Raj Joshi,; Akash Budha Magar,; Sugam Sharma,; Ram Chandra Basnyat,; Sharma, Khaga (Journal of Institute of Science and Technology, 2025)
Colebrookea oppositifolia Sm. is a medicinal shrub traditionally used to treat various ailments, including urinary disorders, skin eruptions, and epilepsy. This study reports the green synthesis of zinc oxide nanoparticles (ZnO NPs) using an aqueous stem extract of C. oppositifolia Sm. The synthesized ZnO NPs were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, ultraviolet-visible (UV-Vis) spectroscopy, field emission scanning electron microscopy (FE SEM), and energy-dispersive X-ray spectroscopy (EDX). UV-Vis analysis of ZnO nanoparticles revealed a peak at 364 nm, while FTIR confirmed the role of plant secondary metabolites in capping, reducing, and stabilizing ZnO NPs. XRD analysis indicated a crystalline structure with an average grain size of 10.89 nm. EDX confirmed the elemental composition of zinc, carbon, and oxygen. The ZnO NPs exhibited strong antibacterial and antifungal activity against Staphylococcus aureus, Shigella sonnei, and Candida albicans. They also demonstrated moderate antioxidant activity and significant anticancer effects against HeLa and A549 cell lines, with IC50 values of 56.6 ± 1 µg/mL and 141.0 ± 0.0548 µg/mL, respectively. These findings highlight the potential of C. oppositifolia Sm. mediated synthesized ZnO NPs for biomedical, industrial, and packaging applications.